2023
DOI: 10.1021/acssuschemeng.3c05127
|View full text |Cite
|
Sign up to set email alerts
|

Green Food Packaging with Integrated Functions of High-Efficiency Radiation Cooling and Freshness Monitoring

Yannan Chen,
Zhuoya Wang,
Yuting Dai
et al.

Abstract: An optimal temperature environment is crucial for ensuring that the freshness of agricultural products is maintained during transportation. However, packaging materials often have a limited ability to dissipate heat and cannot accurately indicate the condition of the products, leading to significant losses in the logistics. Here, in order to achieve the fresh delivery of agricultural products, we constructed a ZnO-nanorods/cellulose membrane-starch membrane@blueberry anthocyanins (ZnO-NRs/CM-SM@BA) packaging m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 45 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Experimental results indicated that utilizing this film for packaging strawberries under direct sunlight can extend their storage time up to 9 days (shown in Figure 7c), demonstrating its potential as a superior solution for food preservation. In further advancements, Chen et al [120] developed a novel packaging material based on ZnO Nanorods/Cellulose Membrane-Starch Membrane@Bilberry Anthocyanins (ZnO-NRs/CM-SM@BA). This packaging material leverages the rod-like structure of ZnO nanorods, exhibiting a visible light reflectance of 94.4% and an IR emissivity of 98.8%, substantially reducing heat intake and enhancing the dissipation of thermal accumulation.…”
Section: Food Preservation and Packagingmentioning
confidence: 99%
“…Experimental results indicated that utilizing this film for packaging strawberries under direct sunlight can extend their storage time up to 9 days (shown in Figure 7c), demonstrating its potential as a superior solution for food preservation. In further advancements, Chen et al [120] developed a novel packaging material based on ZnO Nanorods/Cellulose Membrane-Starch Membrane@Bilberry Anthocyanins (ZnO-NRs/CM-SM@BA). This packaging material leverages the rod-like structure of ZnO nanorods, exhibiting a visible light reflectance of 94.4% and an IR emissivity of 98.8%, substantially reducing heat intake and enhancing the dissipation of thermal accumulation.…”
Section: Food Preservation and Packagingmentioning
confidence: 99%
“…Until now, some research on integrating RC technology for packages has been reported. Chen et al proposed a smart packing material for the fresh delivery of agricultural products, which achieved high visible reflectivity and infrared emissivity of 94.4 and 98.8%, respectively, and realized cooling of 6.5 °C . Xu et al reported a nanocomposite hydrogel packaging with high solar reflectivity and infrared emissivity that can effectively prevent the anthocyanin and trypsin from degradation .…”
Section: Introductionmentioning
confidence: 99%